2011
DOI: 10.53855/bjt.v14i2.200
|View full text |Cite
|
Sign up to set email alerts
|

Terapia De Indução Com Timoglobulina Versus Anticorpo Monoclonal Anti - Il2r - Uma Análise Pareada Em Transplante Renal Com Doador Falecido

Abstract: Introdução: A timoglobulina é um anticorpo policlonal utilizado na terapia de indução em transplante (Tx) renal e que tem sido associado à redução na incidência de função retardada do enxerto (DGF) e rejeição aguda. Objetivo: Comparar terapia de indução com timoglobulina versus anticorpos monoclonais anti-IL2R em uma análise pareada de transplantes renais com doador falecido. Métodos:Todos os rins pareados de doador falecido no período de 2006-2008, onde um dos rins foi alocado para um paciente recebendo timog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…A study carried out in two renal transplant reference centers in Ceará looking at induction therapy with thymoglobulin and basiliximab found prevalence rates of DGF of 56.5% and 63.0%, respectively. 20 de Sandes-Freitas et al 18 and Helfer et al 19 reported rates of DGF in their cohort of 54.2% and 70.8%, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…A study carried out in two renal transplant reference centers in Ceará looking at induction therapy with thymoglobulin and basiliximab found prevalence rates of DGF of 56.5% and 63.0%, respectively. 20 de Sandes-Freitas et al 18 and Helfer et al 19 reported rates of DGF in their cohort of 54.2% and 70.8%, respectively.…”
Section: Discussionmentioning
confidence: 87%